2019
DOI: 10.1002/jcb.29047
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA‐196a improves cognitive impairment and alleviates neuronal damage in hippocampus tissues of Alzheimer's disease through downregulating LRIG3 expression

Abstract: Purpose This study is launched to uncover the inner function of microRNA‐196a (miR‐196a) on cognitive dysfunction and neuronal damage in Alzheimer's disease (AD) rats through regulating the PI3K/Akt signaling pathway. Methods The establishment of AD rat model was performed by a microinjection of Aβ25‐35. miR‐196a and LRIG3 expression was detected, and the putative binding site between them was also determined. The spatial learning and memory capability, the hippocampal neurons ultrastructure as well as the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“… 9 , 10 It is hypothesized that abnormal regulation of miRNA-targeted networks plays a key role in AD pathological processes via regulation of genes involving Aβ overproduction, 11 , 12 , 13 tau hyperphosphorylation, 14 , 15 glial-activation-induced neuroinflammation, 16 , 17 synaptic dysfunction, 18 , 19 and neuronal apoptosis. 20 , 21 Despite reported involvement of novel miRNAs in AD pathogenesis, the identity of sensitive mRNAs involved in the diagnosis, treatment, and pathophysiological implications of AD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 It is hypothesized that abnormal regulation of miRNA-targeted networks plays a key role in AD pathological processes via regulation of genes involving Aβ overproduction, 11 , 12 , 13 tau hyperphosphorylation, 14 , 15 glial-activation-induced neuroinflammation, 16 , 17 synaptic dysfunction, 18 , 19 and neuronal apoptosis. 20 , 21 Despite reported involvement of novel miRNAs in AD pathogenesis, the identity of sensitive mRNAs involved in the diagnosis, treatment, and pathophysiological implications of AD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs also influence several vital neurodevelopmental and adult brain neuronal processes 14,18,19,21 . Moreover, alterations of the miRNAs activity is associated with Alzheimer's 27–35 and Parkinson's diseases 11 . Understanding of the miRNAs systems of neuronal regulation is thus timely and relevant.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miRNAs are critical for neural development 21 and adult neurogenesis, 14,18,19 and memory‐related synaptic plasticity 22,23 . Dysregulation of miRNAs activity is further associated with a wide variety of severely debilitating human neurodegenerative conditions such as epilepsy, 24–26 Alzheimer's 27–35 and Parkinson's diseases 11 …”
Section: Introductionmentioning
confidence: 99%
“…Lin et al (30) used Osthole to upregualte miRNA-101a-3p. Several miRNAs have been reported to be involved in a variety of diseases (16)(17)(18)(19). Because of their stability and endogenous nature, miRNAs may be used as treatment options in AD (31).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous biological processes and >60% human genes are regulated by microRNAs (miR) than can be found in most body tissues, including brain tissues, cerebrospinal fluid and serum ( 15 ). Dysregulation of miRNA is therefore crucial in neurodegenerative diseases ( 16 ). Previous in vitro and in vivo studies have explored the role of miRNAs in the pathogenesis of AD, and demonstrated that miR-92a-3p, miR-181c-5p and miR-210-3p, miRNA-132, miRNA-107 are in abnormal high or low expression level in the brains of patients with AD ( 17-19 ).…”
Section: Introductionmentioning
confidence: 99%